Kondisi Amerika Setelah Perang Dingin Berakhir - Aulia Zahra Yuanita; Eko Ribawati; Tubagus Noeriman Achmad Sumantri (LPPM Politeknik Pratama, 2024)
This research will discuss the end of the Cold War and the important factors that influenced end of the Cold War. There is an opinion that the Cold War was actually an ideological conflict between the Soviet Union and the United States. However, conflicts between superpowers have shaped military confrontations and security policies in the post-World War II world. As a result, many countries, especially the three countries in the world, became victims of the ideological war between the United States and the Soviet Union.